Interpolation of Combined Head and Room Impulse Response for Audio Spatialization - Mehrotra, Sanjeev; Chen, Wei-ge; Zhang, Zhengyou (Proceedings of MMSP, 2011)
Audio spatialization is becoming an important part of creating realistic experiences needed for immersive video conferencing and gaming. Using a combined head and room impulse response (CHRIR) has been recently proposed as an alternative to using separate head related transfer functions (HRTF) and room impulse responses (RIR). Accurate measurements of the CHRIR at various source and listener locations and orientations are needed to perform good quality audio spatialization. However, it is infeasible to accurately measure or model the CHRIR for all possible locations and orientations. Therefore, low-complexity and accurate interpolation techniques are needed to perform audio spatialization in real-time. In this paper, we present a frequency domain interpolation technique which naturally interpolates the interaural level difference (ILD) and interaural time difference (ITD) for each frequency component in the spectrum. The proposed technique allows for an accurate and low-complexity interpolation of the CHRIR as well as allowing for a low-complexity audio spatialization technique which can be used for both headphones as well as loudspeakers.